Permian Stratigraphy and Fusulinida of Afghanistan with Their Paleogeographic and Paleotectonic Implications - Leven, E.Ja. (The Geological Society of America, 1997)
Permian rocks are widespread in Afghanistan and species of the Fusulinida show that all stages of this system from Asselian to Dorashamian are present. All of the species encountered in this study from almost all known Permian exposures in Afghanistan are herein described and figured, including one new genus, Laosella n. gen., and 41 new species and subspecies including Neofusulinella callosa n. sp., N. magna n. sp., Codonofusiella simplex n. sp., Biwaella tumefacta n. sp., Zellia her- itschi afghanica n. subsp., Rugososchwagerina altimurica n. sp., R. heratica n. sp., Dar- vasella ponderosa n. sp., D. cucumeriformis n. sp., Dutkevitchia sourkhobensis n. sp., Darvasites ordinatus longus n. subsp., D. afghanensis n. sp., Chalaroschwagerina bamianica n. sp., C. sourkhobensis n. sp., Pseudofusulina karapetovi n. sp., P. kara- petovi gudriensis n. sp. and n. subsp., P. karapetovi tezakensis n. sp. and n. subsp., P. macilenta n. sp., P. peregrina n. sp., P. fabra grandiuscula n. subsp., P. acuminatula n. sp., P. hessensis orientalis n. subsp., P. heratica n. sp., P. sourkhobensis n. sp., P. priva n. sp., P. bulolensis n. sp., P. argandabensis n. sp., P. immensa n. sp., P. perspicua n. sp., P. haftkalensis n. sp., Praeskinnerella crassitectoria afghanensis n.subsp., Para- fusulina uruzganensis n. sp., Chusenella subextensa n. sp., Rugosochusenella dialis n. sp., Verbeekina (Quasiverbeekina) altimurensis n. sp., Cancellina (Shengella) bami- anica n. sp., Neoschwagerina bamianica n. sp., Colania altimurensis n. sp., Presumat- rina uruzganensis n. sp., P. longa n. sp., and Sumatrina bulolensis n. sp.
Keywords: Afghanistan; Permian Stratigraphy; Fusulinida; Paleozoic::Permian; Палеозой::Пермская